Talas Cripic Packaging Design Using Kansei Engineering And Analytical Hierarchy Process (Ahp) Method: Desain Kemasan Kripik Talas Menggunakan Metode Kansei Engineering Dan Analytical Hierarchy Process (Ahp) - Nasoik, M. Kholisun; Jakaria, Ribangun Bamban; Cahyana, Atikha Sidhi; Putra, Boy Isma (Procedia of Engineering and Life Science, 2023)
One of the MSMEs engaged in the snack food sector and currently running is the taro chips business owned by Mr. Wahab which is located at Tambak Sari Village, Purwodadi Pasuruan, East Java. Business running for 1 year. Chips are snacks or snacks made from various ingredients such as flour and others, and also from tubers. Based on the results of interviews and observations obtained from consumers, the problem that is often complained of is the packaging used, which is thin plastic and easily torn or perforated. So that the condition of the chips is easily sluggish or not crispy. Kansei engineering is a technology that translates a customer's or consumer's feeling and image about a product which is then translated into design elements or in other languages, is a customer-oriented technology for product development based on computer science. The purpose of the Kansei engineering method is to make it easier for designers to gather consumer needs based on feelings or what can be called consumer psychology. The Kansei method will be integrated with the Analytical Hierarchy Process (AHP) to decide whether the new packaging is more feasible and good or not. The results showed that the packaging of taro chips was a simple design, bright color, and plastic material from the Kansei Engineering and AHP methods. The packaging is strong and durable so that it can maintain the crispness of the chips.